Implementasi Sistem Server Lokal Tanpa Kuota untuk Penyediaan Materi Edukasi di Lingkungan Terbatas Akses Internet pada SMKN 1 Bantan - Nur Ilham. A; Agus Tedyyana; Pretti Ristra (STIKes Ibnu Sina Ajibarang, 2025)
Limited internet access in remote areas remains a major obstacle to equitable digital education in Indonesia. This situation significantly impacts student and teacher accessibility to digital learning resources, which are increasingly becoming a necessity in 21st-century learning. One way to address this obstacle is to provide alternative technology infrastructure that does not rely on external internet connections. This study aims to implement and evaluate a local server system without a quota at SMKN 1 Bantan as a solution for providing educational materials in environments with limited network coverage. The local server system is designed to store various learning content, including text, video, and interactive modules, which can then be accessed through the school's internal network. This mechanism allows students and teachers to access materials more quickly and stably, free from quota limitations and dependence on commercial internet networks, which are often slow or unavailable. The implementation results indicate that the local server is able to improve the accessibility and speed of distribution of learning materials. Teachers can easily upload teaching materials, while students can access them anytime through devices connected to the school network. Surveys conducted with students and teachers also indicate a high level of satisfaction with this system. They assessed that local servers facilitated the teaching and learning process, supported student independence, and reduced technical barriers that often arose due to weak internet connections. Furthermore, this study emphasized the importance of utilizing appropriate technology in educational settings in remote areas. Implementing local servers without quotas proved to be a relatively inexpensive, easy-to-manage, and sustainable solution to support equitable digital education.